Regulating the glucose-6-phosphate dehydrogenase encoding gene gsdA and its impact on growth and citric acid production in Aspergillus niger - Susanne Fritsche; Valeria Ellena; Güler Demirbas-Uzel; Matthias G. Steiger (PLoS ONE, 2025)
Glycolysis in A. niger, a key organism in industrial biotechnology, provides essential precursors for efficient citric acid production. Glucose-6-phosphate dehydrogenase (G6PD), encoded by the gene gsdA, is a critical point in the cellular metabolism as it determines the metabolic fate of glucose-6-phosphate by redirecting it into the pentose phosphate pathway (PPP). Despite its decisive position in the metabolic network the functional role of G6PD and its impact on citric acid synthesis and growth is not fully understood. Here, we present an A. niger strain expressing a ptet-on regulated version of gsdA at the pyrG locus. The native gene was disrupted and hence, gsdA expression was based on a single copy level. Under non-inducing conditions, the strain was not growing on glucose. On gluconate, a precursor for an intermediate of the oxidative PPP, growth was restored but delayed compared to the control strain expressing gsdA under the native promoter. Furthermore, citric acid production was monitored in dependency of different gsdA induction levels using doxycycline. At low induction levels, the yield on glucose was enhanced by 49% compared to the control strain, albeit with reduced growth leading to lower titers. Through supplementation of the medium with gluconate, we anticipated to provide precursors for biomass production for efficient metabolization of glucose to citric acid. Without the native regulation of the gsdA gene growth and citric acid production were time delayed. However, the yield of the gsdA-regulated strain was higher compared to the control after 120 h of cultivation and was positively influenced with an increasing proportion of gluconate in the medium. The findings of this study underscore the dependency of growth and citric acid production on gsdA expression in A. niger.